Estimation of total hepatic blood flow by duplex ultrasound. Issue 1 (January 1992) - Carlisle, K M; Halliwell, M; Read, A E; Wells, P N
Abstract : The volume flow rate of blood in the portal vein and the hepatic artery was measured using a duplex ultrasound system. Two sections of the hepatic artery were studied; the common hepatic artery where measurements were made just after the bifurcation of the coeliac axis to splenic and hepatic arteries and the hepatic artery itself, where measurements were made just proximal to the porta hepatis in a straight stretch of artery overlying the portal vein. Total hepatic blood flow was taken as the sum of hepatic artery and portal vein flows. A group of 10 normal healthy volunteers in the fasting state was studied. The mean (SD) volume blood flow in the vessels was measured to be: hepatic artery 3.5 (45%) ml/min/kg, common hepatic artery 6.9 (30%) ml/min+/kg, portal vein 13.5 (21%) ml/min/kg, total hepatic flow 17.0 (16%) ml/min/kg.